Patterns of Labor Market Adjustment to Trade Shocks with Imperfect Capital Mobility - Artuc, Erhan; Brambilla, Irene; Porto, Guido (World Bank, Washington, DC, 2021)
This paper explores how different investment frictions affect the patterns of responses of labor markets to tariff cuts. To investigate these patterns, this paper formulates a multi-sector dynamic model featuring capital and labor adjustment costs that is fitted to Argentine data. Counterfactual simulations of a tariff decline in the textile sector are used to show that capital adjustment can create long-run responses of real wages that are larger than the short-run responses. This happens as textile firms disinvest during the transition. This paper also shows that the reduction of tariffs on capital inputs boosts investment and real wages across sectors. This paper assesses the nature of capital adjustment costs, including fixed, convex, and irreversibility costs in determining these patterns of labor market responses to trade reforms.